I2-mediated sulfonylation and Na2SO3-mediated deacylation: a general protocol for the synthesis of β-keto sulfones and β-dicarbonyl sulfones1. Issue 32 (10th April 2015) - Gao, Wen-Chao; Zhao, Jin-Jin; Hu, Fei; Chang, Hong-Hong; Li, Xing; Wei, Wen-Long
<x xml:space="preserve">Abstract</x> A general method for constructing both β-keto sulfones and β-dicarbonyl sulfones has been developed.